Indigenous natural enemies associated with Phyllocnistis citrella (Lepidoptera: Gracillariidae) in eastern Spain - Urbaneja, Alberto; Llácer, Elena; Tomás, O.; Garrido, Antonio; Jaques, Josep A. (2017)
The incidence of generalist indigenous natural enemies of the citrus leafminer (CLM), Phyllocnistis citrella Stainton (Lepidoptera; Gracillariidae), was monitored during three growing seasons at two different orchards located in the major citrus-growing area of Spain. Composition of the parasitoid complex changed during the study period. However, the eulophids Cirrospilus near lyncus Walker and Pnigalio pectinicornis L. were consistently the predominant species. Despite the varying composition of the parasitoid complex, oviposition, host feeding, and predatory preferences of the natural enemies of the CLM clearly centered on third instar larvae. Incidence of beneficial fauna increased as the season progressed, reaching maximal values up to 70% of susceptible leafminers (mature larvae) at the end of the summer. Parasitism was significantly related to relative host density. However, predation showed no relationship to host availability but did so to flushing in one of the orchards. Incidence of indigenous natural enemies of the CLM should not be ignored when planning any introduction of exotic parasitoids, and their conservation should be taken into account when planning any citrus IPM strategy. (C) 2000 Academic Press.